2022
DOI: 10.3390/su14020935
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption and Bioleaching of Heavy Metals from Electronic Waste Varied with Microbial Genera

Abstract: Industrialization and technological advancements have led to the exploitation of natural resources and the production of hazardous wastes, including electronic waste (E-waste). The traditional physical and chemical techniques used to combat E-waste accumulation have inherent drawbacks, such as the production of harmful gases and toxic by-products. These limitations may be prudently addressed by employing green biological methods, such as biosorption and bioleaching. Therefore, this study was aimed at evaluatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 76 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…The same can be observed for Cu (39–72%), and when using Acidithiobacillus , Sulfobacillus and Ferroplasma , where Cu amounts to 27% [ 69 ], Pleurotus florida (18%) and Pseudomonas spp. (16.6%) [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…The same can be observed for Cu (39–72%), and when using Acidithiobacillus , Sulfobacillus and Ferroplasma , where Cu amounts to 27% [ 69 ], Pleurotus florida (18%) and Pseudomonas spp. (16.6%) [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…There have been many studies investigating the use of different physicochemical methods in removal, reuse and recovery of copper from electronic waste, such as adsorption [ 13 , 14 , 15 , 16 ], incineration [ 17 ], landfill dumping [ 18 ], advanced/chemical oxidation [ 19 ] and precipitation [ 20 ]. Although such approaches could minimize the effect of electronics waste, they nonetheless have limitations [ 21 ] and lack cost-effectiveness. On the other hand, Igiri et al [ 22 ] reported bioleaching that is an eco-friendly technology as a circular economy for extracting valuable divalent metals such as Cu(II) ions from electronic waste [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is an emerging physico-chemical adsorption technique that utilizes certain types of inactive, dead, or viable microbial biomass for the removal of metals from e-waste through complexation, chelation, coordination, and ion-exchange between the metals [12,39]. The microbial cell wall consists of many functional groups, including a carbonyl, phosphodiester, sulfonate, and phosphate group, that are needed for sequestering metals present in e-waste [106,107]. Biomass of several fungal, bacterial, and algal species has been used as a biosorbent for the recovery of heavy metals, precious metals, and rare earth metals from e-waste [12].…”
Section: Biosorptionmentioning
confidence: 99%